Understanding the large inferred Einstein radii of observed low-mass galaxy clusters. Issue 4 (24th April 2020) - Robertson, Andrew; Massey, Richard; Eke, Vincent
ABSTRACT: We assess a claim that observed galaxy clusters with mass 10^14 M_ are more centrally concentrated than predicted in lambda cold dark matter (ΛCDM). We generate mock strong gravitational lensing observations, taking the lenses from a cosmological hydrodynamical simulation, and analyse them in the same way as the real Universe. The observed and simulated lensing arcs are consistent with one another, with three main effects responsible for the previously claimed inconsistency. First, galaxy clusters containing baryonic matter have higher central densities than their counterparts simulated with only dark matter. Secondly, a sample of clusters selected because of the presence of pronounced gravitational lensing arcs preferentially finds centrally concentrated clusters with large Einstein radii. Thirdly, lensed arcs are usually straighter than critical curves, and the chosen image analysis method (fitting circles through the arcs) overestimates the Einstein radii. After accounting for these three effects, ΛCDM predicts that galaxy clusters should produce giant lensing arcs that match those in the observed Universe.